2021
DOI: 10.1007/s00432-021-03697-1
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary apoplexy induced by gonadotropin-releasing hormone (GnRH) agonist administration for treatment of prostate cancer: a systematic review

Abstract: Objective We aimed to review of literature on the clinical presentation, management and outcomes of pituitary apoplexy following gonadotrophic release hormone (GnRH) agonist administration for the treatment of prostate cancer. Methods We used PRISMA guidelines for our systematic review and included all English language original articles on pituitary apoplexy following GnRH agonist administration among prostate cancer patients from Jan 1, 1995 to Dec 31, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…GnRH agonists are commonly used in the management of patients with PCa and can rarely lead to PA 6 11. In a systematic review by Raj et al , authors reported 21 such cases between 1990 and 2020 with only three cases happening in previously known pituitary adenoma 6. In this case, the patient did not have any known pituitary adenoma as suggested by previously normal pituitary imaging and was only found to have abnormal imaging at the diagnosis of PA.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…GnRH agonists are commonly used in the management of patients with PCa and can rarely lead to PA 6 11. In a systematic review by Raj et al , authors reported 21 such cases between 1990 and 2020 with only three cases happening in previously known pituitary adenoma 6. In this case, the patient did not have any known pituitary adenoma as suggested by previously normal pituitary imaging and was only found to have abnormal imaging at the diagnosis of PA.…”
Section: Discussionmentioning
confidence: 87%
“…Although PA commonly happen in setting of known pituitary tumours, in over 60% of cases, the underlying lesion can be diagnosed at the time of apoplectic event 10. GnRH agonists are commonly used in the management of patients with PCa and can rarely lead to PA 6 11. In a systematic review by Raj et al , authors reported 21 such cases between 1990 and 2020 with only three cases happening in previously known pituitary adenoma 6.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations